THE EFFECT OF ABSORBING MATTER ON THE OBSERVED NUMBER OF THE EMBEDDED STARS II - PISMIS, P (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1956)
The effect of absorbing matter on the counted number of stars had been discussed under restricted assumptions in paper I. In this paper the same problem is taken up for a less restricted case. The conclusions are that the ratio in the increase in star num
BOL OBS TONAN TACUB
Keywords: EFFECT, ABSORBING MATTER, OBSERVED NUMBER, EMBEDDED, STARS II; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS